Strategi Instagram Sebagai Digital Marketing Dalam Promosi Kuliner Bir Pletok Alifah Bagi Pelaku UMKM Jakarta Utara - Ido Afriadi; Rofian Dedi Susanto (CV. ITTC INDONESIA, 2025)
This study was conducted (1) To determine the use of Instagram in promoting Alifah plektok beer, UMKM in North Jakarta City. (2) To determine the marketing communication strategy in promoting Alifah plektok beer, UMKM in North Jakarta City through Instagram. This study uses a qualitative method with a case study approach using a triangulation data validity test to obtain the validity of this study. The results of this study are: (1) Instagram has users in the age range of teenagers to adults, where this age is the target market for Alifah plektok beer. The features provided by Instagram are very suitable and can support all planned Alifah plektok beer promotion strategies. Through Instagram, Alifah plektok beer has succeeded in introducing its products to the public, this is in accordance with the concept of UMKM (2) The use of everyday language that is friendly, easy to understand and tends to invite followers to communicate. The relationship with followers/customers is always maintained as well as possible by routinely responding to all forms of incoming feedback, be it in the form of comments from posts or private DMs. This is in accordance with the concept of Communication. Collaboration can expand the target market for Alifah plektok beer, done by collaborating with different UMKM communities. (3) All information about Alifah plektok beer can be accessed and asked directly through the @birplektokalifah account, the admin is always responsive in responding to feedback from followers. The varied content of Alifah plektok beer such as promos, health education gets a positive response from Instagram followers. An increase in the number of transactions always occurs when Alifah plektok beer does a certain discount promo.